Central muscarinic M2 cholinoceptors involved in cholinergic hypertension - (:unkn) unknown (My University, 1993)
Cholinomimetic agents increase blood pressure and heart rate via central muscarinic cholinoceptors in various species. It was reported that i.c.v. injection of the muscarinic M1 and M3 cholinoceptor selective antagonist, 4-DAMP (4-diphenylacetoxy-N-methyl-piperidine methiodide), inhibited the pressor response to physostigmine, while the M1 selective antagonist, pirenzepine, was ineffective. In the present study, the involvement of muscarinic M2 cholinoceptors in central cholinergic hypertension and tachycardia was investigated. Physostigmine (10-80 micrograms/kg i.v.), a cholinesterase inhibitor, and oxotremorine (20-40 micrograms/kg i.v.), a direct muscarinic cholinoceptor agonist, caused a dose-dependent increase in blood pressure. Additionally, physostigmine induced dose-dependent tachycardiac responses. I.c.v. administration of the muscarinic M2 cholinoceptor antagonists, AF-DX 116 and methoctramine, inhibited both physostigmine (60 micrograms/kg) and oxotremorine (20 micrograms/kg)-induced pressor responses at their lower doses used in this study (100 nmol/rat and 10 nmol/rat, respectively). These findings indicate the partial involvement of postsynaptic muscarinic M2 cholinoceptors. The higher doses of the antagonists (AF-DX 116,300 nmol/rat and methoctramine 30 nmol/rat) potentiated the blood pressure increase due to physostigmine but did not affect that due to oxotremorine. The physostigmine-induced tachycardiac responses were influenced similarly by these antagonists. These results suggest the presence and tonic influence of presynaptic inhibitory muscarinic M2 cholinoceptors.
Keywords: Female; Animals; Male; Rats; Blood Pressure; Dose-Response Relationship, Drug; Heart Rate; Pirenzepine; Rats, Sprague-Dawley; Injections, Intraventricular; Physostigmine; Injections, Intravenous; Receptors, Muscarinic; Muscarinic Antagonists; Diamines; Oxotremorine